![1.a)\;\log_2(x^2-2x)=3\\ x^2-2x=2^3\\ x^2-2x-8=0\\ D=36\\ x_1=-2,\'x_2=4\\ b)\;2\log_5(-x)=\log_5(x+2)\\ \log_5(-x)^2=\log_5(x+2)\\ x^2=x+2\\ x^2-x-2=0\\ D=9\\ x_1=-1,\;x_2=2\\ c)\;\log^2_4x-2\log_4x-3=0\\ \log_4x=t,\;\log_4^2x=t^2\\ t^2-2t-3=0\\ D=16\\ t_1=-1,\;t_2=3\\ \log_4x=-1\Rightarrow x=4^{-1}=\frac14\\ \log_4x=3\Rightarrow x=4^3=64 1.a)\;\log_2(x^2-2x)=3\\ x^2-2x=2^3\\ x^2-2x-8=0\\ D=36\\ x_1=-2,\'x_2=4\\ b)\;2\log_5(-x)=\log_5(x+2)\\ \log_5(-x)^2=\log_5(x+2)\\ x^2=x+2\\ x^2-x-2=0\\ D=9\\ x_1=-1,\;x_2=2\\ c)\;\log^2_4x-2\log_4x-3=0\\ \log_4x=t,\;\log_4^2x=t^2\\ t^2-2t-3=0\\ D=16\\ t_1=-1,\;t_2=3\\ \log_4x=-1\Rightarrow x=4^{-1}=\frac14\\ \log_4x=3\Rightarrow x=4^3=64](https://tex.z-dn.net/?f=1.a%29%5C%3B%5Clog_2%28x%5E2-2x%29%3D3%5C%5C+x%5E2-2x%3D2%5E3%5C%5C+x%5E2-2x-8%3D0%5C%5C+D%3D36%5C%5C+x_1%3D-2%2C%5C%27x_2%3D4%5C%5C+b%29%5C%3B2%5Clog_5%28-x%29%3D%5Clog_5%28x%2B2%29%5C%5C+%5Clog_5%28-x%29%5E2%3D%5Clog_5%28x%2B2%29%5C%5C+x%5E2%3Dx%2B2%5C%5C+x%5E2-x-2%3D0%5C%5C+D%3D9%5C%5C+x_1%3D-1%2C%5C%3Bx_2%3D2%5C%5C+c%29%5C%3B%5Clog%5E2_4x-2%5Clog_4x-3%3D0%5C%5C+%5Clog_4x%3Dt%2C%5C%3B%5Clog_4%5E2x%3Dt%5E2%5C%5C+t%5E2-2t-3%3D0%5C%5C+D%3D16%5C%5C+t_1%3D-1%2C%5C%3Bt_2%3D3%5C%5C+%5Clog_4x%3D-1%5CRightarrow+x%3D4%5E%7B-1%7D%3D%5Cfrac14%5C%5C+%5Clog_4x%3D3%5CRightarrow+x%3D4%5E3%3D64)
![d)\;\log_{0,2}(x+1)=\log_{0,2}(8-x)-\log_{0,2}x\\ \log_{0,2}(x+1)=\log_{0,2}\frac{8-x}x\\ x+1=\frac{8-x}x\\ x^2+x=8-x\\ x^2+2x-8=0\\ D=36\\ x_1=-4,\;x_2=2\\ 2.a)\log_3(x-2)<2\\ x-2<9\\ x<7\\ b)\;\log_{0,5}(2x-4)\geq\log_{0,5}(x+1)\\ 2x-4\leq x+1\\ x\leq5\\ c)\;\log_3(x^2-1)<\log_3(x+1)+1\\ \log_3(x^2-1)<\log_3(x+1)+\log_33\\ \log_3(x^2-1)<\log_33(x+1)\\ x^2-1<3x+3\\ x^2-3x-4<0\\ x^2-3x-4=0\\ D=25\\ x_1=-1,\;x_2=4\\ x\in(-1;4) d)\;\log_{0,2}(x+1)=\log_{0,2}(8-x)-\log_{0,2}x\\ \log_{0,2}(x+1)=\log_{0,2}\frac{8-x}x\\ x+1=\frac{8-x}x\\ x^2+x=8-x\\ x^2+2x-8=0\\ D=36\\ x_1=-4,\;x_2=2\\ 2.a)\log_3(x-2)<2\\ x-2<9\\ x<7\\ b)\;\log_{0,5}(2x-4)\geq\log_{0,5}(x+1)\\ 2x-4\leq x+1\\ x\leq5\\ c)\;\log_3(x^2-1)<\log_3(x+1)+1\\ \log_3(x^2-1)<\log_3(x+1)+\log_33\\ \log_3(x^2-1)<\log_33(x+1)\\ x^2-1<3x+3\\ x^2-3x-4<0\\ x^2-3x-4=0\\ D=25\\ x_1=-1,\;x_2=4\\ x\in(-1;4)](https://tex.z-dn.net/?f=d%29%5C%3B%5Clog_%7B0%2C2%7D%28x%2B1%29%3D%5Clog_%7B0%2C2%7D%288-x%29-%5Clog_%7B0%2C2%7Dx%5C%5C+%5Clog_%7B0%2C2%7D%28x%2B1%29%3D%5Clog_%7B0%2C2%7D%5Cfrac%7B8-x%7Dx%5C%5C+x%2B1%3D%5Cfrac%7B8-x%7Dx%5C%5C+x%5E2%2Bx%3D8-x%5C%5C+x%5E2%2B2x-8%3D0%5C%5C+D%3D36%5C%5C+x_1%3D-4%2C%5C%3Bx_2%3D2%5C%5C+2.a%29%5Clog_3%28x-2%29%3C2%5C%5C+x-2%3C9%5C%5C+x%3C7%5C%5C+b%29%5C%3B%5Clog_%7B0%2C5%7D%282x-4%29%5Cgeq%5Clog_%7B0%2C5%7D%28x%2B1%29%5C%5C+2x-4%5Cleq+x%2B1%5C%5C+x%5Cleq5%5C%5C+c%29%5C%3B%5Clog_3%28x%5E2-1%29%3C%5Clog_3%28x%2B1%29%2B1%5C%5C+%5Clog_3%28x%5E2-1%29%3C%5Clog_3%28x%2B1%29%2B%5Clog_33%5C%5C+%5Clog_3%28x%5E2-1%29%3C%5Clog_33%28x%2B1%29%5C%5C+x%5E2-1%3C3x%2B3%5C%5C+x%5E2-3x-4%3C0%5C%5C+x%5E2-3x-4%3D0%5C%5C+D%3D25%5C%5C+x_1%3D-1%2C%5C%3Bx_2%3D4%5C%5C+x%5Cin%28-1%3B4%29)
3\\ \log^2_{0,5}x-2\log_{0,5}x>3\\ \log^2_{0,5}x-2\log_{0,5}x-3=0\\ \log_{0,5}x=t,\;\log^2_{0,5}x=t^2\\ t^2-2t-3=0\\ D=16\\ t_1=-1,\;t_2=3\\ \log_{0,5}x=-1\Rightarrow x=0,5^{-1}=2\\ \log_{0,5}x=3\Rightarrow x=0,5^3=0,125=\frac18\\ x\in(0;\frac18)\cup(2;+\infty)" alt="d)\;\log^2_{0,5}x-\log_{0,5}x^2>3\\ \log^2_{0,5}x-2\log_{0,5}x>3\\ \log^2_{0,5}x-2\log_{0,5}x-3=0\\ \log_{0,5}x=t,\;\log^2_{0,5}x=t^2\\ t^2-2t-3=0\\ D=16\\ t_1=-1,\;t_2=3\\ \log_{0,5}x=-1\Rightarrow x=0,5^{-1}=2\\ \log_{0,5}x=3\Rightarrow x=0,5^3=0,125=\frac18\\ x\in(0;\frac18)\cup(2;+\infty)" align="absmiddle" class="latex-formula">
![3.\\\begin{cases} \log_2(x-y)=3\\ 4^{\log_2\sqrt{x+y}}=10 \end{cases}\Rightarrow \begin{cases} x-y=2^3\\ 2^{2\log_2\sqrt{x+y}}=10 \end{cases}\Rightarrow \begin{cases} x-y=8\\ 2^{\log_2(x+y)}=10 \end{cases}\\ \begin{cases} x-y=8\\ x+y=10 \end{cases}\\ \begin{cases} x=8+y\\ 8+y+y=10 \end{cases}\Rightarrow \begin{cases} x=9\\ y=1 \end{cases} 3.\\\begin{cases} \log_2(x-y)=3\\ 4^{\log_2\sqrt{x+y}}=10 \end{cases}\Rightarrow \begin{cases} x-y=2^3\\ 2^{2\log_2\sqrt{x+y}}=10 \end{cases}\Rightarrow \begin{cases} x-y=8\\ 2^{\log_2(x+y)}=10 \end{cases}\\ \begin{cases} x-y=8\\ x+y=10 \end{cases}\\ \begin{cases} x=8+y\\ 8+y+y=10 \end{cases}\Rightarrow \begin{cases} x=9\\ y=1 \end{cases}](https://tex.z-dn.net/?f=3.%5C%5C%5Cbegin%7Bcases%7D+%5Clog_2%28x-y%29%3D3%5C%5C+4%5E%7B%5Clog_2%5Csqrt%7Bx%2By%7D%7D%3D10+%5Cend%7Bcases%7D%5CRightarrow+%5Cbegin%7Bcases%7D+x-y%3D2%5E3%5C%5C+2%5E%7B2%5Clog_2%5Csqrt%7Bx%2By%7D%7D%3D10+%5Cend%7Bcases%7D%5CRightarrow+%5Cbegin%7Bcases%7D+x-y%3D8%5C%5C+2%5E%7B%5Clog_2%28x%2By%29%7D%3D10+%5Cend%7Bcases%7D%5C%5C+%5Cbegin%7Bcases%7D+x-y%3D8%5C%5C+x%2By%3D10+%5Cend%7Bcases%7D%5C%5C+%5Cbegin%7Bcases%7D+x%3D8%2By%5C%5C+8%2By%2By%3D10+%5Cend%7Bcases%7D%5CRightarrow+%5Cbegin%7Bcases%7D+x%3D9%5C%5C+y%3D1+%5Cend%7Bcases%7D)